Tuturan Ekspresif dalam Film Jembatan Pensil Karya Hasto Broto - Hastuti, Hastuti; Anggraini, Tri Riya; Halimah, Supi Nur (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2025)
This study aims to describe expressive speech in the film Jembatan Pensil. The method used in this study is a qualitative descriptive approach. The data source used is the film Jembatan Pensil. Data analysis techniques use data reduction, data presentation, and data conclusions. The results of expressive speech found in the film Jembatan Pensil are 22 data with details: speech expressing gratitude totaling 11 data, speech apologizing totaling 5 data, speech praising totaling 4 data, and speech expressing condolences totaling 2 data.